ISLAMIC SPIRITUAL PERSPECTIVE: MARKETING 4.0 STRATEGY FOR MICRO SMALL AND MEDIUM ENTERPRISES - Wikaningtyas , Suci Utami; Haq , Mujahidain Badi’ul; Muhammadare , Waeno; Yudiawati, Hana (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2023)
Micro, Small, and Medium Enterprises (MSMEs) have numerous vulnerabilities and challenges as a result of significant environmental fluctuations. In order to ensure their survival and profitability, it is imperative for Micro, Small, and Medium Enterprises (MSMEs) to adapt their business strategies. Based on preliminary findings, it is evident that marketing tactics have a crucial role in the success of micro, small, and medium enterprises (MSMEs). Hence, the objective of this research is to identify a proficient and successful marketing approach for Micro, Small, and Medium Enterprises (MSMEs) in the current context. The employed research methodology encompasses a comprehensive literature review coupled with a SWOT analysis. The study's results indicate that micro, small, and medium enterprises (MSMEs) encounter a greater number of weaknesses and obstacles compared to their strengths and opportunities. Furthermore, it is observed that MSMEs predominantly employ marketing strategies aligned with marketing 1.0 and marketing 2.0. Consequently, it is recommended that MSMEs adopt a marketing 4.0 strategy to address these challenges. Furthermore, it is advisable for Micro, Small, and Medium Enterprises (MSMEs) to adopt an Islamic Spiritual-based marketing 4.0 approach, considering that around 87.02 percent of Indonesia's population adheres to the Islamic faith.